Dermoscopic clues to differentiate facial lentigo maligna from pigmented actinic keratosis. (20th January 2016) - Lallas, A.; Tschandl, P.; Kyrgidis, A.; Stolz, W.; Rabinovitz, H.; Cameron, A.; Gourhant, J.Y.; Giacomel, J.; Kittler, H.; Muir, J.; Argenziano, G.; Hofmann‐Wellenhof, R.; et al.
Summary: Background: Dermoscopy is limited in differentiating accurately between pigmented lentigo maligna (LM) and pigmented actinic keratosis (PAK). This might be related to the fact that most studies have focused on pigmented criteria only, without considering additional recognizable features. Objectives: To investigate the diagnostic accuracy of established dermoscopic criteria for pigmented LM and PAK, but including in the evaluation features previously associated with nonpigmented facial actinic keratosis. Methods: Retrospectively enrolled cases of histopathologically diagnosed LM, PAK and solar lentigo/early seborrhoeic keratosis (SL/SK) were dermoscopically evaluated for the presence of predefined criteria. Univariate and multivariate regression analyses were performed and receiver operating characteristic curves were used. Results: The study sample consisted of 70 LMs, 56 PAKs and 18 SL/SKs. In a multivariate analysis, the most potent predictors of LM were grey rhomboids (sixfold increased probability of LM), nonevident follicles (fourfold) and intense pigmentation (twofold). In contrast, white circles, scales and red colour were significantly correlated with PAK, posing a 14‐fold, eightfold and fourfold probability for PAK, respectively. The absence of evident follicles also represented a frequent LM criterion, characterizing 71% of LMs. Conclusions: White and evident follicles, scales and red colour represent significant diagnostic clues for PAK. Conversely, intense pigmentation and grey rhomboidal lines appear highly suggestive of LM. Abstract : What's already known about this topic? Dermoscopy is insufficient to differentiate between lentigo maligna (LM) and pigmented actinic keratosis (PAK). What does this study add? White and evident follicles, scales and red colour represent significant diagnostic clues for PAK. Intense pigmentation and grey rhomboidal lines appear highly suggestive of LM. These novel findings might improve the early detection of LM, while reducing unnecessary biopsies for PAK.